Production of Representative Spaces in Architectural Education through Instrumentalization of the Concepts of Ekphrasis and Hermeneutic - Ozlem SENYIGIT (Anı Publishing, 2021)
Nowadays, architecture has been inquiring about the production of meaning and representation in architecture in addition to building technology and spatial organization. In this study, the ekphrasis and hermeneutics reading methods, which were acquired from different disciplines, were used and analyzed as instruments for producing representative space in architectural education. This study aims to use the concept of ekphrasis as an instrument, which transfers meaning between written representation and the production of representative spaces. In this context, the spaces mentioned in the novel by Ayn Rand entitled "The Fountainhead" were transformed into representative spaces using hermeneutics reading by the students of architecture. In a sense, this study aims to create the fusion of horizons between the the author's discourses about the architectural environment in the novel and the reader (students of architecture). It was observed that this study enabled the establishment of a strong bridge among the student, space, and literature. Each new concept, such as ekphrasis and hermeneutics, would add new meanings to the instrumentation design education and enrich the styles of thinking and performing.